3-3 piezoelectric metamaterial with negative and zero Poisson's ratio for hydrophones applications. (April 2019) - Khan, Kamran A.; Khan, Muhammad Ali
Graphical abstract: Highlights: Electromechanical properties of novel 3D elastically anisotropic and piezoelectrically active metamaterial are introduced. Electromechanical properties of metamaterial based on the three classes of HC structures with negative and zero Poisson's ratio are presented. Employed intrinsic symmetry of metamaterial architecture to derive and validate simplified mixed boundary conditions equivalent to PBCs. Extraordinary values of hydrostatic figure of merits are observed for 3D HC networks indicating their suitability for hydrophones. Light weight actuator and sensors with tunable properties can be realized with the proposed metamaterial architecture. Abstract: This study presents the electromechanical properties of the 3-3 piezoelectric metamaterial based on variants of honeycomb (HC) structure. Three kinds of three-dimensional (3D) elastically anisotropic and piezoelectrically active HC structures were introduced, namely, conventional HC (3D-CHC), a re-entrant HC (3D-RE) and a semi-re-entrant HC (3D-SRE). Highly porous 3D finite element models of the mentioned three kinds of metamaterials were developed and the role of ligament orientation on their effective elastic, piezoelectric and dielectric properties was completely characterized. The intrinsic symmetry of HC structure was utilized and simplified mixed boundary conditions equivalent to periodic boundary conditions were recognized. In comparison to their bulk constituent, all the 3-3 type piezoelectric HC networks exhibited an enhanced response, especially for the longitudinal poling. The normalized figures of merit show a mild dependence on the angle θ and the underlying deformation mechanisms associated with the zero, positive and negative Poisson's ratios. Figures of merit such as hydrostatic strain coefficient ( d h ), the hydrostatic figure of merit ( d h . g h ) and the acoustic impedance ( Z ) reached their best values at small angles, i.e., θ = 30°. Longitudinally poled networks exhibited four order of magnitude increase in their hydrostatic figure of merit (foam to solid ratio >10, 000) and one order of magnitude decrease in the acoustic impedance indicating their applicability for the design of hydrophones.